2021
DOI: 10.1136/bcr-2020-241048
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune pulmonary alveolar proteinosis and idiopathic pulmonary haemosiderosis: a dual pathology

Abstract: Pulmonary alveolar proteinosis (PAP) is a rare pulmonary condition which leads to excessive accumulation of proteinaceous material within the alveoli. Idiopathic pulmonary haemosiderosis (IPH) is another orphan lung disease and results in recurrent alveolar haemorrhage. This case study describes a case of these two rare pathologies occurring together. A man in his 50s presented with a 6-week history of haemoptysis and worsening dyspnoea. A CT scan of the thorax showed multifocal, bilateral ground glass opacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A total of 60 studies that fulfilled the inclusion criteria were identified [ 2 , 11 , 14 - 69 ]. Figure 1 illustrates the study selection process.…”
Section: Reviewmentioning
confidence: 99%
“…A total of 60 studies that fulfilled the inclusion criteria were identified [ 2 , 11 , 14 - 69 ]. Figure 1 illustrates the study selection process.…”
Section: Reviewmentioning
confidence: 99%
“…Five patients were positive for autoantibodies (cohort A) [ 18 - 22 ], and the rest were tested but turned out to be negative for any antibodies (cohort B). The mean (SD) and median (IQR) ages at diagnosis of IPH for cohort A were 58.2 (19.9) years and 50 (36.5) years, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…Of note, 5/38 (13.2%) patients tested positive for an autoantibody. Two of these patients were positive for ANA [ 20 , 21 ], two for antithyroid antibody [ 19 , 21 ], and one patient each tested positive for ANCA [ 21 ], RF [ 18 ], and GM-CSF antibody [ 22 ]. Two of these five patients also tested positive for CD antibodies [ 20 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations